Absolute Beginner's Guide to Programming, Third Edition - Perry, Greg (Que, 2002)
No prior programming experience necessary! Absolute Beginner¿s Guide to Programming helps readers understand what programming really is. Readers not only get an overview of the job of programming, but also learn which specific skills are needed for certain jobs. Coverage includes how a computer interprets a program¿s instructions with insight into what goes on "under the hood" when a computer runs a program, how programming can and does relate to the Internet and the skills required for adding security to programs, and compiled versus interpreted languages like JavaScript and HTML. Absolute Beginner¿s Guide to Programming offers "hands on" programming for the "absolute beginner". Though there are hundreds of books for beginners about specific languages, this is the only book that takes today's programming environments and explains why each is important and where each works best.